Exercise Training positively modulates the Ectonucleotidase Enzymes in Lymphocytes of Metabolic Syndrome Patients - Martins, C. C.; Bagatini, M. D.; Cardoso, A. M.; Zanini, D.; Abdalla, F. H.; Baldissarelli, J.; Dalenogare, D. P.; dos Santos, D. L.; Schetinger, M. R. C.; Morsch, V. M. M. (International Journal of Sports Medicine, 2016)
In this study, we investigated the cardiovascular risk factors as well as ectonucleotidase activities in lymphocytes of metabolic syndrome (MetS) patients before and after an exercise intervention. 20 MetS patients, who performed regular concurrent exercise training for 30 weeks, 3 times/week, were studied. Anthropometric, biochemical, inflammatory and hepatic parameters and hydrolysis of adenine nucleotides and nucleoside in lymphocytes were collected from patients before and after 15 and 30 weeks of the exercise intervention as well as from participants of the control group. An increase in the hydrolysis of ATP and ADP, and a decrease in adenosine deamination in lymphocytes of MetS patients before the exercise intervention were observed (P<0.001). However, these alterations were reversed by exercise training after 30 weeks of intervention. Additionally, exercise training reduced the inflammatory and hepatic markers to baseline levels after 30 weeks of exercise. Our results clearly indicated alteration in ectonucleotidase enzymes in lymphocytes in the MetS, whereas regular exercise training had a protective effect on the enzymatic alterations and on inflammatory and hepatic parameters, especially if it is performed regularly and for a long period.
Keywords: metabolic syndrome; E-NTPDase; ADA; exercise training; inflammation